Arresting the Sword of Damocles: Dating the Transition to the Post-Malthusian Era in Denmark - Peter Sandholt Jensen; Maja Uhre Pedersen; Cristina Victoria Radu; Paul Richard Sharp (European Historical Economics Society (EHES), 2020)
Unified Growth Theory postulates a transition from a Malthusian to a post-Malthusian era and finally to modern economic growth. Previous studies have been able to date the end of the post-Malthusian era, but none have conclusively established the timing of the end of the Malthusian era and thus transition to the post-Malthusian era. We consider the case of Denmark, which was characterized by extreme resource and environmental constraints until the final decades of the eighteenth century and thus presents a good candidate for a purely Malthusian society. We employ a cointegrated VAR model on Danish data from ca. 1733-1800, finding that evidence for diminishing returns, which characterize the "pure" Malthusian era, disappears after 1775, consistent with an increasing pace of technological progress.
Keywords: J1; N33; O4; 330; Cointegration; Denmark; Malthusian; post-Malthusian